Referring physicians' intention to use hospital report cards for hospital referral purposes in the presence or absence of patient-reported outcomes: a randomized trial - Martin Emmert; Anja Schindler; Laura Heppe; Uwe Sander; Christiane Patzelt; Michael Lauerer; Eckhard Nagel; Cornelia Frömke; Oliver Schöffski; Cordula Drach (The European Journal of Health Economics, 2023)
Purpose: This study aims to determine the intention to use hospital report cards (HRCs) for hospital referral purposes in the presence or absence of patient-reported outcomes (PROs) as well as to explore the relevance of publicly available hospital performance information from the perspective of referring physicians. Methods: We identified the most relevant information for hospital referral purposes based on a literature review and qualitative research. Primary survey data were collected (May–June 2021) on a sample of 591 referring orthopedists in Germany and analyzed using structural equation modeling. Participating orthopedists were recruited using a sequential mixed-mode strategy and randomly allocated to work with HRCs in the presence (intervention) or absence (control) of PROs.Results: Overall, 420 orthopedists (mean age 53.48, SD 8.04) were included in the analysis. The presence of PROs on HRCs was not associated with an increased intention to use HRCs ( p 0.167em=0.167em0.316). Performance expectancy was shown to be the most important determinant for using HRCs (path coefficient: 0.387, p 0.167em<0.167em.001). However, referring physicians have doubts as to whether HRCs can help them. We identified "complication rate" and "the number of cases treated" as most important for the hospital referral decision making; PROs were rated slightly less important. Conclusions: This study underpins the purpose of HRCs, namely to support referring physicians in searching for a hospital. Nevertheless, only a minority would support the use of HRCs for the next hospital search in its current form. We showed that presenting relevant information on HRCs did not increase their use intention.
Keywords: I12; 610; Public reporting; Hospital referrals; Patient-reported outcomes; UTAUT; Hospital report cards